Peran Masjid Imadudding Jl. Sabang No. 17 Bandung dalam Pembinaan Masyarakat - Syfa Nur Malawati; Wildan Yahya (Jurnal Riset Komunikasi Penyiaran Islam, 2022)
Abstract-This study is against the background of the importance of community knowledge about the role of mosques in community building. The purpose of this study is to know the role of the mosque in the spiritual development of the community, to know the role of the Imaduddin mosque in Islamic preaching to the community, to know the role of the Imaduddin mosque in the economic empowerment of the community, and to know the role of the mosque in education for the community. The method used in this research is a qualitative method using a descriptive approach. Data were obtained from interviews with mosque administrators and people living around the Imaduddin mosque. The results of the study show the role of Imaduddin mosque for the surrounding community not only as a place of worship vertically, Imaduddin Mosque has other roles for the community including spiritual development of the community, Islamic preaching to the community, economic empowerment of the community, and education for the community. The role of the Imaduddin Mosque has been in line with the function and role of the mosque in building society. Abstract-Penelitian ini dilatar belakangi oleh pentingnya pengetahuan masyarakat mengenai peranan masjid dalam membina masyarakat. Tujuan dari penelitian ini untuk mengetahui peran masjid dalam pembinaan spiritual masyarakat, mengetahui peran masjid Imaduddin dalam dakwah Islamiyyah kepada masyarakat, mengetahui peran masjid Imaduddin dalam pemberdayaan ekonomi masyarakat, dan mengetahui peran masjid dalam pendidikan bagi masyarakat. Metode yang digunakan pada penelitian ini yaitu metode kualitatif dengan menggunakan pendekatan deskriptif. Data didapatkan dari hasil wawancara dengan pengurus masjid dan masyarakat yang tinggal di sekitar masjid Imaduddin. Hasil dari penelitian menunjukan peranan masjid Imaduddin untuk masyarakat sekitar bukan hanya sebagai tempat ibadah secara vertikal saja, Masjid Imaduddin memiliki peranan lain untuk masyarakat diantaranya pembinaan spiritual masyarakat, dakwah Islamiyyah kepada masyarakat, pemberdayaan ekonomi masyarakat, dan pendidikan bagi masyarakat. Peran Masjid Imaduddin telah sesuai dengan fungsi dan peranan masjid dalam pembinaan masyarakat.